Perempuan dalam Komunikasi Pembangunan Pertanian di Sumba Timur - Listiorini, Dina (Jurnal ILMU KOMUNIKASI, 2014)
Abstract: This paper discusses womenÃ¢â¬â¢s problem in the communication process of agricultural development in Kadahang, Wunga and Napu, the villages in Haharu distric, East Nusa Tenggara province. In the context of agricultural development, woman should be an important subject who is actively engaged. However, the women in Sumba are still trapped in patriarchal culture. The biggest agricultural problem of Haharu people is water deficiency. In dealing with this problem, women in Sumba remain as objects and passive participants. The absence of mass media as a result of the absence of electricity in the district makes it worse.Abstrak: Tulisan ini mendiskusikan masalah perempuan dalam proses komunikasi pembangunan pertanian di desa Kadahang, Wunga dan Napu yang terletak di kecamatan Haharu, provinsi Nusa Tenggara Timur. Perempuan dalam konteks pembangunan pertanian seharusnya menjadi subjek yang penting dalam proses partisipasi pembangunan. Namun, perempuan di Sumba masih terkurung dalam budaya patriarkat yang tidak memungkinkan mereka berpartisipasi secara penuh dalam proses pembangunan pertanian. Persoalan masyarakat terbesar di kecamatan Haharu adalah kekurangan air. Menghadapi masalah ini pun, perempuan masih berada dalam tataran objek dan partisipan yang pasif. Ketiadaan media massa sebagai dampak dari ketiadaan listrik di kecamatan tersebut memperparah keadaan tersebut.